Resolusi Nonlitigasi atas Penolakan Wali Perkawinan: Peran Penghulu sebagai Mediator - M. Amri Pratama; Irwan (Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the efforts of marriage registrars (penghulu) in resolving marriages that are not approved by the guardian (wali) in Galang District. This research employed a qualitative approach with a field research design. Data were collected through in-depth interviews, observation, and documentation involving three marriage registrars who had experience in handling cases of guardians refusing to approve their daughters’ marriages. The findings indicate that no cases of wali adhal officially determined by the Religious Court have occurred in the Office of Religious Affairs (KUA) of Galang District. However, there was a case in which a guardian initially refused to act as the marriage guardian, and the issue was successfully resolved through mediation, persuasive communication, religious counseling, and family deliberation. The marriage registrars played a significant role as mediators by facilitating communication between the guardian, the prospective bride, and family members to reach a mutual agreement. The refusal of guardians was generally influenced by family conflicts, post-divorce disputes, and personal considerations regarding the prospective groom. This study concludes that marriage registrars perform not only administrative duties but also strategic roles in safeguarding family welfare through non-litigation dispute resolution before cases proceed to the Religious Court